我国小模数弧齿锥齿轮制造技术综述 - 罗建勤; 汪慧君; 吕传贵 (Jixie chuandong)
Firstly,the present situation and problems of small module spiral bevel gear in China manufacturing technology are expounded from the process technology and standard of accuracy and so on,the opportunity and challenge faced in the manufacturing technology of small spiral bevel gearare analyzed.Itis pointed outthatupgrading and innovation of the manufacturing technology including the high accuracy and high strength,gear ratio reductiongearand green manufacturingwill become the core powersupply of transformation and upgradingof the small gearindustry product structure.